Perancangan Strategi Perawatan di PT. INTEGRA INDOKABINET - Sumawi, Hendrik; Halim, Siana (Jurnal Titra, 2013)
In this research we constructed suitable maintenance strategy for double end machine in PT. Integra Indokabinet. We applied Reliability Centered Maintenance based on Dempster â Shafer theory. Additionally, we used historical data and interviewing the expert staff in that company. The most suitable strategy for each failure are scheduled maintenance for v-belt and thermis failure, reinstal part for sekring kaca failure and condition based maintenance for footswitch failure.